Addressing the Limitations of the Futures Cone: Introducing the Adaptive Futures Mesh - Alireza Hejazi (Foresight and STI Governance)
This paper aims to address the limitations of traditional strategic foresight methodologies, specifically the Futures Cone (FC), by introducing and evaluating a novel framework called the Adaptive Futures Mesh (AFM). The study employs a conceptual analysis, drawing on systems thinking, complexity science, and participatory design principles to develop the AFM. The AFM is structured around key components including a dynamic mesh network, uncertainty gradients, adaptive feedback loops, and an emergence engine. The analysis finds that the AFM offers a more robust approach to navigating uncertainty by explicitly incorporating unknown unknowns (dark matter nodes). It visualizes cascading impacts, emphasizing human agency, and enables continuous adaptation through feedback loops. Research limitations include the lack of empirical validation and potential challenges in implementing the AFM across diverse contexts. However, the AFM offers significant practical implications for strategic planning. It enables organizations to move beyond prediction and cultivate futures-readiness. Socially, the AFM promotes more inclusive and equitable futures by democratizing foresight and empowering stakeholders to shape their own destinies. The originality and value of this paper lie in its articulation of a novel, adaptive framework that enhances strategic resilience in facing complexity and multiple crises.